Analisis Kemampuan Guru-Guru Kimia SMA Sumatera Utara Dalam Mengintegrasikan TPACK - Ani Sutiani; Zainuddin Muchtar; Ratu Evina Dibyantini; Marudut Sinaga; Jamalum Purba (Universitas Negeri Medan, 2022)
These 21st century skills are not inborn skills, but are acquired from experience. Therefore, educators must condition learning in such a way that all aspects of these 21st century skills can be trained, one of which is by using digital learning. The specific objectives of this study were to: (1) obtain a mapping or analysis of the needs of Chemistry teachers in integrating TPACK in learning, (2) measure the level of ability of Chemistry teachers in integrating TPACK in learning, (3) analyze the needs of Chemistry teachers in developing models. digital based Chemistry learning to develop students' abilities in the 21st century. This research is a quasi-experimental research by adopting the ADDIE model development research procedure. The results showed that the ability of chemistry teachers to integrate TPACK in learning based on the responses given by teachers from 12 cities/districts in North Sumatra was grouped into 7 components, namely: TK (Technological Knowledge) = 76.47%; PK (Paedagogical Knowledge) = 83.68%; CK (Content Knowledge) = 80.88%; TPK (Technological Pedagogical Knowledge) = 75.29%; PCK (Paedagogical Content Knowledge) = 78.97%; TCK (Technological Content Knowledge) = 83.14%; and TPACK (Technological Pedagogical Content Knowledge) = 80.47 %. This means that the overall ability of chemistry teachers to integrate TPACK in learning is categorized as capable and quite capable.Keterampilan abad ke- 21 ini bukan keterampilan yang dibawa sejak lahir, melainkan diperoleh dari pengalaman. Oleh karena itu, pendidik harus mengondisikan pembelajaran sedemikian rupa agar semua aspek dari keterampilan abad ke-21 tersebut dapat dilatihkan, salah satunya dengan menggunakan pembelajaran digital. Tujuan khusus dari penelitian ini adalah untuk: (1) mendapatkan pemetaan atau analisis kebutuhan kemampuan guru Kimia dalam mengintegrasikan TPACK dalam pembelajaran, (2) mengukur tingkat kemampuan guru Kimia dalam mengintegrasikan TPACK dalam pembelajaran, (3) melakukan analisis kebutuhan guru Kimia dalam mengembangkaan model pembelajaran Kimia berbasil digital untuk mengembangkan kemampuan siswa pada abad 21. Penelitian ini merupakan penelitian eksperimen semu dengan mengadopsi prosedur penelitian pengembangan model ADDIE. Hasil penelitian menunjukkan bahwa kemampuan guru kimia dalam mengintegrasikan TPACK dalam pembelajaran berdasarkan respon yang diberikan guru dari 12 kota/kabupaten di Sumatera Utara dikelompokkan dalam 7 komponen, yaitu: TK (Technological Knowledge) = 76,47%; PK (Paedagogical Knowledge) = 83,68%; CK (Content Knowledge) = 80,88%; TPK (Technological Paedagogical Knowledge) = 75,29%; PCK (Paedagogical Content Knowledge) = 78,97 %; TCK (Technological Content Knowledge) = 83,14%; dan TPACK (Technological Paedagogical Content Knowledge) = 80,47 %. Hal ini berarti secara keseluruhan kemampuan guru kimia dalam mengintegrasikan TPACK dalam pembelajaran termasuk kategori mampu dan cukup mampu.